Sustainable entrepreneurship and new business models: a market research in Colombia - Sanchez-Hernandez, María Isabel; Dorado-Mayorga, Elena; Pereira-Alvarez, Guillermo Alberto; Osorio-Atehortua, Ubeimar; Malavera-Pineda, Sandra; Montoya-Quintero, Jaime Alberto (Revista de Administração da UFSM, 2020)
Purpose –The aim of this work is to approach the concept of sustainable entrepreneurship from a theoretical and a practical point of view, paying attention to new business models that are emerging around the world for social innovation. In this context, we focus the attention on the business model called one-for-one and we wonder whether the Colombian market should be a good option for developing this business model. Design/methodology/approach – To test the viability of the business model one-for-one we conducted a market research in March 2019, with a sample of students from two higher education institutions in the city of Medellin (Colombia). Findings – The results of the empirical research show the positive moral attitude of Colombian to solve social problems, but also the market immaturity because of the relative low purchase intentions found in Colombian potential consumers. Research limitations/implications– Not exempt from criticism, this work defends innovative business models standing for a business driven concept of sustainability which focusses on increasing both economic as well as social value. Practical implications – The model of donating one item to someone in need, for each item purchased, could be considered in the future a viable option for developing business models in Colombia. Social implications – Nowadays and more than never before, society requires that the actions of companies are aimed at contributing to social development and environmental sustainability, as well as economic viability. Companies oriented towards present and future sustainability in the decision making of purchase or investment will be an important source of competitive advantages in the near future. Originality/value – Although the study of sustainable entrepreneurship is still in very early stages in Latin American countries, this work shed light on the topic analyzing the business model one-for-one as a potential mean to foster a transition towards more sustainable societies.